Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1524-475x.2012.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant pain relief with an ibuprofen‐releasing foam dressing: Results from a randomized, controlled, double‐blind clinical trial in exuding, painful venous leg ulcers

Abstract: The objective of this 6-week, 120-patient, double-blind, randomized, controlled trial was to investigate if a foam dressing with ibuprofen provided clinically relevant pain relief (PAR) for exuding, painful venous leg ulcers in comparison with a similar foam dressing without ibuprofen. Primary outcome parameter was PAR compared with baseline pain during the first 5 days of the investigation. PAR was registered by the patient morning and evening. Main end point was proportion of patients reporting a summed PAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Therefore, to obtain rapid pain relief, dressings loaded with drugs, such as local anesthetics (e.g., lidocaine), or NSAIDs can be very useful to reduce wound pain during wear time and dressing change. In particular, ibuprofen has excellent local effects on superficial wounds, without detectable systemic levels and provide clinically relevant pain relief for patients with exuding, painful venous ulcers . In a multicenter randomized controlled trial, Arapoglou et al examined the analgesic effect (over 5 days) of foam dressings loaded with ibuprofen (112.5 mg) compared with local best practice wound management in various wound types (arterial, venous and mixed arterial‐venous ulcers, vasculitis and traumatic ulcers).…”
Section: Drug‐containing (Delivery) Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to obtain rapid pain relief, dressings loaded with drugs, such as local anesthetics (e.g., lidocaine), or NSAIDs can be very useful to reduce wound pain during wear time and dressing change. In particular, ibuprofen has excellent local effects on superficial wounds, without detectable systemic levels and provide clinically relevant pain relief for patients with exuding, painful venous ulcers . In a multicenter randomized controlled trial, Arapoglou et al examined the analgesic effect (over 5 days) of foam dressings loaded with ibuprofen (112.5 mg) compared with local best practice wound management in various wound types (arterial, venous and mixed arterial‐venous ulcers, vasculitis and traumatic ulcers).…”
Section: Drug‐containing (Delivery) Dressingsmentioning
confidence: 99%
“…In particular, ibuprofen has excellent local effects on superficial wounds, without detectable systemic levels 174 and provide clinically relevant pain relief for patients with exuding, painful venous ulcers. [175][176][177][178] In a multicenter randomized controlled trial, Arapoglou et al 175 examined the analgesic effect (over 5 days) of foam dressings loaded with ibuprofen (112.5 mg) compared with local best practice wound management in various wound types (arterial, venous and mixed arterial-venous ulcers, vasculitis and traumatic ulcers). They showed that the ibuprofen releasing foam dressing produced a significantly higher analgesic effect than the local best practice group based on patient scores.…”
Section: Anti-inflammatory and Analgesic Dressingsmentioning
confidence: 99%
“…[30][31][32] Mostly NSAIDs are taken through systemic administration (i.e., in the form of pills), whereas several approaches have been and are researched towards their integration into different wound dressing formulations. [33][34][35][36] Although antibiotics are not the preferred type of drugs for local treatment due to possible resistance acquisition of commensal bacteria, there are several interesting studies available about preparation of dressing, combining NSAIDs and antimicrobials. [37][38][39] The purpose of this study was therefore to prepare wound dressing materials with incorporated NSAIDs and to study their efficiency related to material performance and drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations found after topical administration, however, are only a fraction of the levels found following oral administration. Recently, an evaluation of the effect of ibuprofen in the form of a foam dressing (Biatain Ibu) on persistent and temporary wound pain underwent clinical trials [ 13 17 ]. The ibuprofen foam dressing was shown to consistently relieve wound pain in exuding wounds of various etiologies, irrespective of basal pain intensity.…”
Section: Introductionmentioning
confidence: 99%